BIFUNCTIONAL ELECTROCATALYST COFeNi-MF/NF WITH HIGH ELECTROCHEMICALLY ACTIVE SURFACE: SYNTHESIS, MORPHOLOGICAL ANALYSIS AND ECSA ASSESSMENT. (Scientific journal of the Fergana State University, 2026)
In this work, the morphological, structural, and electrochemical properties of the CoFeNi-MF/NF nanocomposite, synthesized by the hydrothermal method and modified with magnetic fluid, were studied. Nickel foam was selected as the electrode substrate, on the surface of which a nanocomposite consisting of metal salts Co, Fe, and Ni was formed. SEM images revealed the formation of a multilayer porous structure in the form of leaf-like and needle-like particles on the surface of the synthesized material. Based on EDS analysis, it was confirmed that Co, Fe, Ni, and O are evenly distributed on the substrate surface. Electrochemical activity was assessed in an alkaline medium of 1 M KOH. Using the cyclic voltammetry method, the values of double capacitance were determined as 58.2 and 32.84 mF·cm−2 for the hydrogen and oxygen evolution reaction, respectively. High electrochemically active surface area indicates the promising nature of this nanocomposite as a bifunctional catalyst with high electrochemical activity in hydrogen and oxygen evolution reactions. These results confirm that the improvement of nanostructured materials based on CoFeNi through liquid magnetic modification can become an important basis for the development of a new generation of effective electrocatalysts in hydrogen energy.